Electoral democracy and civil war - Bartusevičius, Henrikas; Skaaning, Svend-Erik (Politica, 2016)
The democratic civil peace hypothesis has generated considerable debate in conflict research. This debate has centered on three general claims: democracies have lower risk of civil conflict; autocracies have as low a risk of civil conflict as democracies; and hybrid regimes have the highest risk of civil conflict. This study reassesses the relationship between regime type and civil conflict by employing the newly constructed Lexical Index of Electoral Democracy (LIED). This measure enables us both to distinguish between levels of electoral democracy and distinct regime types. In contrasts to previous studies, our global statistical analysis shows that hybrid regimes do not have the highest risk of civil conflict. Rather, full autocracies are the most conflict prone, while full electoral democracies are least likely to experience civil conflict.